Upaya Meningkatkan Kompetensi Pengelola Perpustakaan Melalui Kegiatan Komunitas SLiMS Kediri Raya - Muhammad Hamim (IJAL (Indonesian Journal of Academic Librarianship), 2018)
The fast development of library technology has forced librarians and information managers to continually improve their competencies. In order to enhance their skills, ones can participate in both formal and informal education. One of the informal ways of sharpening skills is to engage in communities. SLiMS Kediri Raya Community is a community which concerns on sharpening their members’ librarianship skills, primarily in enhancing their library IT skills. There are several activities held by the community which include gathering day, workshops or training session, library automation consultation and guidance, and online learning through social media. It is hoped that by participating in those activities, the community members who majority did not have any librarianship educational backgrounds will be able to improve their skills and competencies in the field.